Packaging fortified with Natamycin nanoparticles for hindering the growth of toxigenic Aspergillus flavus and aflatoxin production in Romy cheese - Fayed, Asmaa; Elsayed, Huda; Ali, Taghreed (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study assessed the effect of cellulose sheets fortified with Natamycin-loaded alginate nanoparticles on the growth of toxigenic Aspergillus flavus and aflatoxin production on the superficial layer of Egyptian Romy cheese after 12 weeks of maturation. Materials and Methods: Toxigenic A. flavus (GenBank accession No. MT645073) was inoculated into the outer surface of Egyptian Romy cheese (at 5 log CFU/gm) and wrapped with a cellulose sheet fortified with Natamycin-loaded alginate nanoparticles. Unwrapped control contaminated Romy wheels were made as well as non-contaminated wrapped cheese wheels for sensory evaluation. Romy cheese wheels were stored at a temperature similar to commercial methods for 12 weeks. Fungal counts were enumerated during this time, and enzyme-linked immune sorbent assay detected aflatoxin after the 4th week of maturation storage. Results: In cheese samples covered with cellulose sheets containing Natamycin-loaded alginate nanoparticles, the fungal count was reduced by 2 log approximately in contrast to control samples after the 2nd week of storage. However, within the 8th week of storage, the greatest significant reduction (p < 0.05) was seen where fungal growth was hindered entirely to the end of the ripening period. The mean values for taste, color, flavor, and overall acceptability were 4, 4.7, 4.09, and 4.3, respectively. Furthermore, in the treated samples, the total aflatoxin concentration was decreased by 78.6% relative to the untreated control one. Conclusion: Using cellulose sheets fortified with Natamycin-loaded alginate nanoparticles in Egyptian Romy cheese wrapping could be an effective way of controlling A. flavus and subsequent aflatoxin production without influencing the typical taste, color, flavor, and overall appearance of traditional Romy cheese. J. Adv. Vet. Anim. Res., 8(1): 58-63, Mar 2021 http://doi.org/10.5455/javar.2021.h485